2022
DOI: 10.1186/s12968-021-00842-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of adenosine stress cardiovascular magnetic resonance perfusion imaging in patients with MR-conditional transvenous permanent pacemakers and defibrillators

Abstract: Background The use of stress perfusion-cardiovascular magnetic resonance (CMR) imaging remains limited in patients with implantable devices. The primary goal of the study was to assess the safety, image quality, and the diagnostic value of stress perfusion-CMR in patients with MR-conditional transvenous permanent pacemakers (PPM) or implantable cardioverter-defibrillators (ICD). Methods Consecutive patients with a transvenous PPM or ICD referred fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…To this end, Pavon et al recently described a more universal approach of asynchronous pacing in all individuals with >1% pacing on device interrogation, set to 10 bpm above the resting heart rate. 5 The group reported safety of this approach with good image quality in CMRconditional devices and high correlation with subsequent coronary angiography in cases of perfusion defects identified. They further reported no changes in heart rate or systolic blood pressure and a significant decrease in diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To this end, Pavon et al recently described a more universal approach of asynchronous pacing in all individuals with >1% pacing on device interrogation, set to 10 bpm above the resting heart rate. 5 The group reported safety of this approach with good image quality in CMRconditional devices and high correlation with subsequent coronary angiography in cases of perfusion defects identified. They further reported no changes in heart rate or systolic blood pressure and a significant decrease in diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A more universal device reprogramming protocol would have appeal in streamlining tests for this patient population. To this end, Pavon et al recently described a more universal approach of asynchronous pacing in all individuals with >1% pacing on device interrogation, set to 10 bpm above the resting heart rate 5 . The group reported safety of this approach with good image quality in CMR‐conditional devices and high correlation with subsequent coronary angiography in cases of perfusion defects identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequacy of vasodilator stressor response is conventionally tracked by using rise of heart rate ≥10 bpm or fall of systolic blood pressure (SBP) > 10 mmHg as hemodynamic markers of adequacy 5 . However, as confirmed by Miller et al 2 in this issue of the Journal , in keeping with a prior study, 6 such thresholds for change in heart rate and SBP are not reliably observed in CIED patients who have been programmed to asynchronous pacing at 10 bpm above usual heart rate for the duration of CMR imaging with adenosine 2,6 or regadenoson 2 . These conventional hemodynamic markers of adequacy of vasodilator stressor challenge therefore cannot be applied in this clinical scenario, of CIED patients programmed to asynchronous pacing at 10 bpm above usual heart rate for the duration of CMR imaging with adenosine or regadenoson.…”
mentioning
confidence: 91%